“Eventually, I Admitted, ‘I Cannot Do This Alone’”: Exploring Experiences of Suicidality and Help-Seeking Drivers Among Australian Men - Seidler, Zac E.; Wilson, Michael J.; Oliffe, John L.; Kealy, David; Toogood, Nicholas; Ogrodniczuk, John S.; Rice, Simon M. (Frontiers in Sociology, 2021)
While research has explored the intersection between masculinities and men’s experiences of suicidality, comparatively little attention has been paid to the stories surrounding suicidal men’s decision to seek help. The ways in which men experiencing suicidal thoughts and behaviors embody masculinities alongside their enlistment of mental health services remains largely unknown. The present study explored 262 Australian men’s stories surrounding the impetus for help-seeking for suicidal thoughts and behaviors. The sample comprised men ranging in age from 17 to 74 years (M = 40.99; SD = 15.92 years), with most participants residing in a metropolitan area (55.3%), employed full time (43.1%), non-indigenous (95.4%) and heterosexual (73.7%). Participants elaborated on their reasons for help-seeking via an open-text qualitative survey, delivered as part of a larger study exploring help-seeking experiences of Australian men. Thematic analysis of responses generated four themes highlighting the diversity of experience across men, with some highlighting impacts of emasculating early trauma(s) on their suicidality, while others reflected an impulsiveness tied to situational stressors that fractured their masculine identity (e.g., relationship breakdown; job loss). Many men had epiphanies as they reached the limits of their self-reliance and came to terms with their need for help. As their suicidality was witnessed by—and began to impact—those around them, the sight of their previously masked pain by others often facilitated their help-seeking journey. The present findings underscore the complex and multifactorial role of masculinities in men’s suicidality and their paths to help-seeking. Important inroads for future public mental health promotion efforts are discussed, in terms of leveraging self-reliant and caring masculinities in helping men to develop healthy coping in the context of suicidality.